Earnings prospects for low-paid workers higher than for the unemployed but only in high-pay areas with high unemployment - Alexander Plum; Gundi Knies (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
There is considerable debate on whether the prospects of entering a high-paid job are better for those in low-paid jobs compared to the unemployed. Whilst some scholars argue that there is a scarring effect of unemployment others highlight that low pay might signal a low productivity and furthermore reduce the time searching for a better paid job. Using longitudinal data for working age men in England matched with local labor market indicators, we estimate several random-effects probit models and find no difference in the probability of becoming high-paid employed between low-paid workers and the unemployed in areas with low unemployment. However, in areas with high unemployment and high pay, low-paid workers have a higher probability of entering high-paid employment than the unemployed. Moreover, there is a penalty for low-wage workers compared to the unemployed in low-pay areas in their probability of entering high-paid employment.
Keywords: J64; J62; J31; 330